Hacer el pensamiento visible para el fortalecimiento de las habilidades comunicativas en inglés de niños de transición - Marín Hine, Sebastián Fernando; Rodríguez de Martínez, María Nuria (Colombian Applied Linguistics Journal, 2021)
The purpose of this research was to strengthen the communication skills in English of transition children in a private school in Bucaramanga (Colombia). The transition level according to the Ministry of National Education of Colombia (Decreto 3870 de 2006) is the educational offer for children 5 years of age or older. The development of this project was approached from the design of a didactic sequence, using as a theoretical basis the Visible Thinking approach for the development and promotion of mind dispositions through the implementation of Thinking routines, as well as the Natural Language approach for the development of the communicative competence. The data collection was made from the documentation generated from the thinking routines, notes in the field diary, photographic and audiovisual material. The data collected show the link between language and the production of thought, seeing the acquisition of the English language as a functional tool in the improvement of the mother tongue. The research revealed four findings: First, the mother tongue plays an important role in the acquisition of a foreign language. Second, the process of reading and writing in a second language is closely related to the competence that the individual has in their native language. Third, the thinking routines work as scaffolding tools in the internalization of vocabulary and understanding of grammatical structures.